Application of Point Tracking Technology in 360 Degree Panorama Virtual Tour Applications for Introduction to Siliwangi University Campus - Muhammad Adi Khairul Anshary; Cecep Muhamad Sidik Ramdani; Euis Nur Fitriani Dewi; Andi Nur Rahman; Rezi Syahriszani (Universitas Negeri Medan, 2023)
Most of the campus area introduction media use brochures to provide information to prospective students. This media among teenagers is no longer attractive. Most prospective students prefer information through multimedia such as short videos. Due to the limited time of video media, very little content is provided so that delivery will be very less. The use of Virtual Tour 360 multimedia technology will help to provide clear information in the form of text and the application of Point tracking technology will make it easier for users to feel like they are in a campus environment. The methodology used in making this application is the Luther-Sutopo version of the Multimedia Development Life Cycle (MDLC). The 360 Degree Panorama Virtual Tour Application Introduction to the Siliwangi University Campus is expected to make it easier to convey information that can be easily accepted by users. This application can see a real environment simulation on the Siliwangi University campus by representing information in the form of 360° panoramic images making it easy to display information visually. The test results obtained from the alpha test of the application of Point tracking can make it easier for users to run the application and the beta test results that the application functions very well get a score of 83.75%.